Natural deep eutectic solvents-mediated extractions: The way forward for sustainable analytical developments - Fernández, María de Los Ángeles (2018)
The concept of sustainable development has impacted in analytical chemistry changing the way of thinking processes and methods. It is important for analytical chemists to consider how sample preparation can integrate the basic concepts of Green Chemistry. In this sense, the replacement of traditional organic solvents is of utmost importance. Natural Deep Eutectic Solvents (NADES) have come to light as a green alternative. In the last few years, a growing number of contributions have applied these natural solvents proving their efficiency in terms of extraction ability, analyte stabilization capacity and detection compatibility. However, the arising question that has to be answered is: the use of NADES is enough to green an extraction process? This review presents an overview of knowledge regarding sustainability of NADES-based extraction procedures, focused on reported literature within the timeframe spanning from 2011 up to date. The contributions were analyzed from a green perspective in terms of energy, time, sample and solvent consumption. Moreover, we include a critical analysis to clarify whether the use of NADES as extraction media is enough for greening an analytical methodology; strategies to make them even greener are also presented. Finally, recent trends and future perspectives on how NADES-based extraction approaches in combination with computational methodologies can contribute are discussed.